2013
DOI: 10.1007/s10142-013-0326-3
|View full text |Cite
|
Sign up to set email alerts
|

The Lesion Simulating Disease (LSD) gene family as a variable in soybean response to Phakopsora pachyrhizi infection and dehydration

Abstract: The Lesion Simulating Disease (LSD) genes encode a family of zinc finger proteins that are reported to play an important role in the hypersensitive response and programmed cell death (PCD) that are caused by biotic and abiotic stresses. In the present study, 117 putative LSD family members were identified in Viridiplantae. Genes with one, two, or three conserved LSD domains were identified. Proteins with three LSD domains were highly represented in the species analyzed and were present in basal organisms. Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 66 publications
0
19
0
1
Order By: Relevance
“…Several genes involved in HR have been identified in different species (Cabreira et al 2013;Liao et al 2014;Wu et al 2014;Eck et al 2014;Kumar et al 2014). In certain plantpathogen interactions, the development of PCD seems to be mediated by metacaspases (Fig.…”
Section: The Role Of the Metacaspase Gene Family In Plant Stress Respmentioning
confidence: 99%
“…Several genes involved in HR have been identified in different species (Cabreira et al 2013;Liao et al 2014;Wu et al 2014;Eck et al 2014;Kumar et al 2014). In certain plantpathogen interactions, the development of PCD seems to be mediated by metacaspases (Fig.…”
Section: The Role Of the Metacaspase Gene Family In Plant Stress Respmentioning
confidence: 99%
“…The LSD family was initially identified in Arabidopsis thaliana by the analysis of mutants that spontaneously form necrotic lesions in the absence of pathogenic infection (Dietrich et al 1994). Genes belonging to this family negatively regulate PCD under stress conditions (Dietrich et al 1997;Epple et al 2003) and are exclusive to Viridiplantae (Cabreira et al 2013). The A. thaliana LSD1 gene (AtLSD1) is the well-characterized member of this family and acts as a cellular hub that makes a central contribution to the oxidative stress response (Kaminaka et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The role of AtLSD1 in the regulation of cellular signaling homeostasis, photosynthesis, water use efficiency, and seed yield has recently been reported (Wituszynska et al 2013). Additionally, the gene OsLSD1 (Oryza sativa LSD1) regulates PCD and callus differentiation ; OsLOL2 (Oryza sativa LSD1-like 2) is involved in rice growth and disease resistance (Bhatti et al 2008;Xu and He 2007); BohLOL1 (Bambusa oldhamii LDS1-like 1) (Yeh et al 2011) participates in growth and biotic stress response in bamboo, and GmLSD1 to GmLSD8 (Glycine max LSD) are modulated in response to fungi and dehydration stresses (Cabreira et al 2013). These studies have demonstrated the involvement of LSD members in important biological processes in plants, especially responses to abiotic and biotic stresses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations